effect of varicocele treatment on human sperm plasma membrane integrity and pregnancy rate in infertile men after varicoceloctomy - Kouti, Bassim (University of Thi-Qar Journal of Science, 2010)
This study was designed to evaluate the results of semen parameters and hypo-osmotic swelling (HOS) test for semen samples of infertile patients with and without varicocele undergoing intra-uterine insemination (IUI) techniques. Twenty-four semen sample from infertile patients with varicocele and fifty-four without varicocele were collected by masturbation and evaluated after and before in vitro sperm activation.  Spermatozoa prepared by conventional layering technique by using 1ml of the liquefied semen were layered beneath a culture medium (IVF medium). The HOS test was performed after and before in vitro sperm preparation by mixing 0.1 ml of semen with 1.0 ml of a 150 mOsm/ L NaCl as a hypo-osmotic solution. Sperm function tests (SFT) including sperm concentration, sperm motility (%), progressive sperm motility (%), and normal sperm morphology (%) were evaluated according to standard World Health Organization (WHO)criteria and subjected to HOS test. For IUI, the sperm prepared and incubated for 30 minutein 5% CO at 37ºC after in vitro sperm preparation. The results of the present study reported that successful pregnancy rates was more chance  for semen sample with normal HOS test scores than abnormal HOS test.